Improving Students’ Writing Skill in Writing Paragraph through an Outline Technique - Kartawijaya, Sukarta (Kopertis Wilayah X (Sumbar, Riau, Jambi, dan Riau Kepulauan), 2018)
This research was classroom action research. Classroom action research was a research that was conducted by a teacher in order to find out solutions of any problems found during teaching and learning process. In this research, it was done to explain whether by using an outline technique could improve the students’ writing paragraph and also to investigate some factors that influenced the students in writing descriptive paragraph. This research was done at grade VIII B of SMP Negeri 6 Sungai Penuh in academic year 2017/2018. From the result of the test in this research, the result was increased in cycle and two. In cycle one, the mean score was 58.25% and it increased to 76.87%, it increased 18.63% point. It meant that teaching writing through outline improved the students’ writing skill. The improvements were also improved on the result of each sub-indicators of writing test between cycle 1 and 2.